Psychometric properties of the Disturbing Dream and Nightmare Severity Index–Korean version - Lee, Ruda (J Clin Sleep Med, 2021)
STUDY OBJECTIVES: This study aimed to examine psychometric properties of the Disturbing Dream and Nightmare Severity Index (DDNSI) in individuals aged between 18 and 39. METHODS: All participants (n = 674) were asked to complete the DDNSI, including the modified Nightmare Effects Survey. Additionally, 109 participants were tested for test-retest reliability after 3 months. Among our sample, 229 (33.9%) reported having at least 1 nightmare per month. RESULTS: Internal consistency was evaluated for the total sample (Cronbach’s α = .920) and separately for individuals reporting more than once per month (Cronbach’s α = .755). Test-retest reliability after 3 months was .705. Convergent validity of the DDNSI with Nightmare Effects Survey was also satisfactory (r = .638, P < .001). Finally, exploratory factor analysis was conducted to explore the construct of the DDNSI, and results indicated that it consisted of 2 factors, nightmare frequency and nightmare distress [χ(2)(df) = 2.241(1) ∆χ(2) (∆df) = 155.575(4), Tucker-Lewis incremental fit index = .980, root mean square error of approximation (90% confidence interval) = .074 (0, .208), standardized root-mean-square residual = .011]. CONCLUSIONS: The DDNSI is a reliable measure of nightmare severity that can be used in various settings. CITATION: Lee R, Krakow B, Suh S. Psychometric properties of the Disturbing Dream and Nightmare Severity Index–Korean version. J Clin Sleep Med. 2021;17(3):471–477.